Pengembangan Desa Wisata Religi Berbasis Budaya Lokal di Desa Nyatnyono - Rahmadani, Anisya; Gunawan, Gunawan (Umbara, 2023)
This research aims to describe the process to develop religious tourism to increase the village economic productivity by a Village-Owned Enterprises (BUMDes) of Nyatnyono Village. The village owns a local religious and cultural legacy that are potential for religious tourism sector and sustainable economic reservoir. In order to gain a deep understanding of the process, this research employed qualitative-descriptive approach. Data were collected through interviews with local stakeholders, field observations, and analysis of related documents. The research finds that Nyatnyono Village, as a religious tourism destination, has various religious sites that are attractive to tourists so that they can encourage the community’s economic productivity. It creates a new dimension for a holistic work culture and community economic independence; and depicted in the management of village terminals, parking areas, charity boxes, and the sale of various local products, all managed under the auspices of Village-Owned Enterprises (BUMDes). However, there are also several obstacles in the process to develop a religious tourism in the village, such as inadequate infrastructure, lack of community knowledge and skills in tourism management, and a lack of effective promotion and marketing. Strategies that include active collaboration with related parties, such as local governments, religious communities and community leaders are still needed.Keywords: BUMDES, Community Productivity, Religious Tourism Villages.